MARKETING COMMUNICATION AND ACCOUNTING SYNERGIES: MAXIMISING CAMPAIGN ROI - Arif Nugraha Kurniadi; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
In an increasingly competitive digital era, companies are required to optimise every aspect of their operations, including marketing campaigns. Marketing communications plays a role in designing and delivering effective messages, while accounting provides critical financial analysis. The integration of these two fields enables more informed decision-making in resource allocation, media selection, and campaign strategy. By combining marketing creativity and accounting precision, companies can create campaigns that not only capture consumer attention but also generate measurable economic value.